Pediatric Emergency Medicine Asynchronous E‐learning: A Multicenter Randomized Controlled Solomon Four‐group Study. (24th August 2014) - Chang, Todd P.; Pham, Phung K.; Sobolewski, Brad; Doughty, Cara B.; Jamal, Nazreen; Kwan, Karen Y.; Little, Kim; Brenkert, Timothy E.; Mathison, David J.; Burton, John
Abstract Objectives Asynchronous e‐learning allows for targeted teaching, particularly advantageous when bedside and didactic education is insufficient. An asynchronous e‐learning curriculum has not been studied across multiple centers in the context of a clinical rotation. We hypothesize that an asynchronous e‐learning curriculum during the pediatric emergency medicine (EM) rotation improves medical knowledge among residents and students across multiple participating centers. Methods Trainees on pediatric EM rotations at four large pediatric centers from 2012 to 2013 were randomized in a Solomon four‐group design. The experimental arms received an asynchronous e‐learning curriculum consisting of nine Web‐based, interactive, peer‐reviewed Flash/HTML5 modules. Postrotation testing and in‐training examination (ITE) scores quantified improvements in knowledge. A 2 × 2 analysis of covariance (ANCOVA) tested interaction and main effects, and Pearson's correlation tested associations between module usage, scores, and ITE scores. Results A total of 256 of 458 participants completed all study elements; 104 had access to asynchronous e‐learning modules, and 152 were controls who used the current education standards. No pretest sensitization was found (p = 0.75). Use of asynchronous e‐learning modules was associated with an improvement in posttest scores (p < 0.001), from a mean score of 18.45 (95% confidence interval [CI] = 17.92 to 18.98) to 21.30 (95% CI = 20.69 to 21.91), a large effect (partial η2 = 0.19). Posttest scores correlated with ITE scores (r2 = 0.14, p < 0.001) among pediatric residents. Conclusions Asynchronous e‐learning is an effective educational tool to improve knowledge in a clinical rotation. Web‐based asynchronous e‐learning is a promising modality to standardize education among multiple institutions with common curricula, particularly in clinical rotations where scheduling difficulties, seasonality, and variable experiences limit in‐hospital learning.